Optimization Of Minimum Orders For Cookies Production To Achieve Maximum Profits Using Branch And Bound Method - Ambarsari, Ida Fitriana; Fadia, Virotun Nisaul (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
In order to maintain business continuity, the cookie production business requires several steps by creating a strategy for allocating cookie production after receiving orders and also promotions. This is because entrepreneurs often receive consumer requests that do not match their profit targets. Therefore, this research was carried out to determine the minimum number of orders that must be received for one production of cookies to achieve profits. To find out this, considering that the profit, production factors and products produced are closely related to linear programming, researchers used the linear programming method. This research was conducted to find out the optimal consumer demand to achieve profits so as not to experience losses in one production of cookies at Nur’s Cookies House Business. This research uses a case study type of research where the calculation process uses linear program calculation, namely the simplex method and the branch and bound method. The solution obtained is a combination of consumer requests or consumer orders that must be accepted by the Nur’s Cookies House Business to carry out one production, namely 1 recipe of Monde Jam, 1 recipe of Mawaran, and 1 recipe of Nastar to get a maximum profit of Rp 420.000,-.